FACTORS THAT INFLUENCE THE USE OF ACCOUNTING INFORMATION IN MICRO, SMALL, AND MEDIUM ENTERPRISES - khansa sumayah; Nila Aprila (SEAN Institute, 2023)
The purpose of this research is to find out factors that can influence the use of accounting information in MSMEs. Using quantitative research methods by testing hypotheses and analyzing data using SPSS 29. Using primary data in the form of a Likert scale questionnaire, which was conducted on MSMEs in Bengkulu City with a sample of 98 MSMEs. Where the research results show that the perceptions of MSME actors about accounting, business scale and work motivation influence the use of accounting information. Meanwhile, accounting knowledge and business experience have no effect on the use of accounting information.